Superconducting 63-pole 2 Tesla wiggler for Canadian Light Source - Khruschev, S.V.; Kuper, E.A.; Lev, V.H.; Mezentsev, N.A.; Miginsky, E.G.; Repkov, V.V.; Shkaruba, B.A.; Syrovatin, V.M.; Tsukanov, V.M. (Вопросы атомной науки и техники, 2006)
A superconducting 63-pole wiggler with the average period 34 mm designed and fabricated at the Institute of Nuclear Physics in Novosibirsk for Synchrotron Radiation Center (CLS) in Canada is described. The maximum field 2.2 Tesla in the median plane has been achieved. The liquid helium consumption less than 0.03 liters per hour in operating mode has been reached. In January 2005, the wiggler was installed in the storage ring in CLS and now experiments are already underway. The main parameters of the magnet and the cryogenic systems as well as test results are presented.